An exposition of the different approaches in teaching writing through class-newsletter production / Yusof Haji Mustapha and Sharifah Shakirah Alqadree (Universiti Teknologi MARA, Terengganu, 1992)
Over the years rapid changes in the approach to teaching writing have taken place in the English Language classroom. The approach in teaching writing today is different from what it was back in the 60s and early 70s. The rapid shift in approaches to language and language teaching from audio visual to cognitive approach and then to communicative methodologies, have been reflected in the teaching of writing. Now the move is on again, in search for an even better method in the teaching of writing.